Identification of Scan Signatures on Thesis Certification Sheet with Haar Wavelet and Euclidean Distance Method - Rumini, Rumini; Norhikmah, Norhikmah (Journal of Advanced Computing Technology and Application (JACTA), 2019)
A signature is a person’s official identity that can be used for authorization in the field of education, for example, authorization in the form of a ratification of a student’s thesis exam. However, there are cases of students who fake examiners’ signatures using an original signature scanned. To check the library cannot do it in real-time, because of a lack of human resources. Therefore, a system that can identify the thesis or thesis validation sheet collected by students to the library requires original signatures or scans using the Haar wavelet method and Euclidean Distance. The results of this study are Haar Wavelet and Euclidean Distance methods capable of identifying scan signatures on the thesis or thesis examination validation sheet.